The effect of service quality on customer retention through customer satisfaction: The Malaysian fast food industry perspective - Damianus Aludah (2004)
The current research was conducted to examine the influence of the service quality dimensions using the five (5) dimensions of SERVQUAL (Parasuraman et. al., 1988) namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy as the measurement of perceived service quality on Customer Retention through Customer Satisfaction in the fast-food industry in Sabah. The results provide support for the theory that there are significant positive relationships between the five dimensions of service quality and customer satisfaction on the one hand and between the five dimensions of service quality and customer retention through customer satisfaction on the other hand.